HUBUNGAN TINGKAT PENDIDIKAN DENGAN PENERAPAN DETEKSI DINI KEHAMILAN BERESIKO OLEH KADER POSYANDU DI DESA JATEN, KARANGANYAR - Suwarnisih Suwarnisih; Eka Novitayanti (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2022)
ABSTRACT The problem of maternal and child health is still a crucial problem in Indonesia because MMR and The problem of maternal and child health is still a crucial problem in Indonesia because MMR and IMR are an indicator of the welfare of a nation. The government has made various improvement efforts but has not made significant progress. The problem of maternal mortality and infant mortality is related to various factors such as access, human resources, population (level of education, socio-cultural factors, poverty, purchasing power and population density), as well as policies that regulate and strive for affordability of access to health human resources and policies on population (PP IBI, 2016). The purpose of this study was to determine the relationship between education level and implementation of early detection of risky pregnancies by Posyandu cadres in Jaten Village, Karanganyar. Analytical observational research method with a cross sectional approach. The population in this study was 192 posyandu cadres in Jaten village, the sampling technique used was